2020
DOI: 10.1007/s10334-020-00834-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-contrast coronary magnetic resonance angiography: current frontiers and future horizons

Abstract: Coronary magnetic resonance angiography (coronary MRA) is advantageous in its ability to assess coronary artery morphology and function without ionizing radiation or contrast media. However, technical limitations including reduced spatial resolution, long acquisition times, and low signal-to-noise ratios prevent it from clinical routine utilization. Nonetheless, each of these limitations can be specifically addressed by a combination of novel technologies including super-resolution imaging, compressed sensing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 139 publications
(272 reference statements)
0
17
0
Order By: Relevance
“…By applying the 3D free-breathing method to wholeheart coronary magnetic resonance angiography (CMRA), several studies have attempted to improve the assessment of coronary artery stenosis and provide an accurate diagnosis of clinically significant lesions (6). Previous studies had confirmed that both 1.5 T NCE-CMRA and 3.0 T contrast-enhanced coronary magnetic resonance (CE-CMRA) can detect coronary artery stenosis (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…By applying the 3D free-breathing method to wholeheart coronary magnetic resonance angiography (CMRA), several studies have attempted to improve the assessment of coronary artery stenosis and provide an accurate diagnosis of clinically significant lesions (6). Previous studies had confirmed that both 1.5 T NCE-CMRA and 3.0 T contrast-enhanced coronary magnetic resonance (CE-CMRA) can detect coronary artery stenosis (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…CMRA offers a radiation and contrast-free alternative for the evaluation of CAD, particularly for patients who can maintain a heart rate of less than 70 beats per minute. Additional benefits, including the simultaneous acquisition of anatomical and functional data combined with the lack of calcium blooming artifact, make CMRA a preferable choice in a variety of scenarios, including patients with chronic renal failure who are more prone to high coronary calcification burden [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In children, radiation reduction is of paramount importance due to the detrimental effects that cumulative radiation exposure may have on a child’s development and risk of cancer. Kawasaki disease, which requires monitoring for evaluation of coronary aneurysms, can result in high radiation exposure in children as coronary CTA has been the predominant surveillance method [ 41 ]. The Japanese Circulation Society guidelines support using coronary MRA over coronary CTA for monitoring Kawasaki patients to reduce radiation exposure, a recommendation initially made by the society in 2013.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a sufficient fat suppression is important in order to differentiate small vessels from surrounding fatty tissue. The presented sequence also was combined with compressed sensing, which allows for an even shorter acquisition time without decreasing the spatial resolution [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%